Pengembangan E-Restaurant Menggunakan Metode Scrum untuk Meningkatkan Kualitas Pelayanan - Ali Rahman; Agung Triayudi; Eri Mardiani (KITA Institute, 2023)
The culinary industry is a business that is experiencing very fast growth. Technology simplifies all activities in management so that data presentation is faster and more accurate. The application of technology helps increase the effectiveness of the business processes being carried out. The restaurant business in using technology is needed to simplify the ordering process, submit data, process payments, make reports more innovative and efficient. This application was developed using agile method as needed which has many changes. This development simplifies the process of customer ordering and payment transactions for satisfaction with the service system provided so as to improve performance more effectively and efficiently.